Harga Saham Ditinjau dari Perspektif Inflasi dan Nilai Tukar Rupiah pada Indeks Saham Syariah Indonesia (ISSI) Sektor Industri Barang Konsumsi Tahun 2014–2018 - Nani Rohaeni; Rini Fitriani Pamila (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2022)
Stock prices are a very important factor and must be considered by investors in making investments because stock prices show the issuer's performance. The ups and downs of stock prices are affected by internal and external factors. The purpose of this study is to determine and examine the Influence of Inflation and Rupiah Exchange Rate on Stock Prices partially and simultaneously in the Consumer Goods Industry Sector in the Indonesian Sharia Stock Index (ISSI) period 2014-2018. This study used a quantitative approach. The population in this study were 29 companies registered in ISSI for the 2014-2018 period. The sample used is 7 out of 29 companies with the sampling technique that is purposive sampling. The results in this study indicated that the effect of inflation on stock prices produces a t-count (minus) greater than t table (minus) (-1,916> -2,037). While the effect of the Rupiah Exchange Rate on stock prices produces a t-value greater than t table (6,594> 2,037) and F (simultaneous) test results are obtained that Inflation and the Rupiah Exchange Rate on Stock Prices with a F value greater than F table (93.633> 3.29). Conclusions in this study indicated that partially Inflation does not have a significant effect on Stock Prices, while the Rupiah Exchange Rate has a significant effect on Stock Prices and simultaneously Inflation and Rupiah Exchange Rate have a influence significant on Stock Prices.